Post-translational Mechanisms Regulating NK Cell Activating Receptors and Their Ligands in Cancer: Potential Targets for Therapeutic Intervention - Molfetta, Rosa; Zingoni, Alessandra; Santoni, Angela; Paolini, Rossella (Frontiers in Immunology, 2019)
Efficient clearance of transformed cells by Natural Killer (NK) cells mainly depends on the recognition of “induced self” ligands by several activating receptors, including NKG2D, NCRs, and DNAM1. The surface expression of these receptors as well as their specific ligands is finely regulated during malignant transformation through the integration of different mechanisms acting on transcriptional, post-transcriptional and post-translational levels. Among post-translational mechanisms, the release of activating ligands in the extracellular milieu through protease-mediated cleavage or by extracellular vesicle secretion represents some relevant cancer immune escape processes. Moreover, covalent modifications including ubiquitination and SUMOylation also contribute to negative regulation of NKG2D and DNAM1 ligand surface expression resulting either in ligand intracellular retention and/or ligand degradation. All these mechanisms greatly impact on NK cell mediated recognition and killing of cancer cells and may be targeted to potentiate NK cell surveillance against tumours. Our mini review summarizes the main post-translational mechanisms regulating the expression of activating receptors and their ligands with particular emphasis on the contribution of ligand shedding and of ubiquitin and ubiquitin-like modifications in reducing target cell susceptibility to NK cell-mediated killing. Strategies aimed at inhibiting shedding of activating ligands and their modifications in order to preserve ligand expression on cancer cells will be also discussed.